AB0569 THE EFFECT OF CUTANEOUS AND MUSCULOSKELETAL SYMPTOMS ON QUALITY OF LIFE IN PATIENT WITH SYSTEMIC LUPUS ERYTHEMATOSUS IN RENAISSANCE COHORT. (June 2019) - Vorobyova, Lyubov; Aseeva, Elena; Solovyev, Sergey
Abstract : Background: Cutaneous and musculoskeletal symptoms is one of the most frequent clinical complaints of patients with systemic lupus erythematosus(SLE) and has been found to occur in up to 70%-95% of patients during the course of the disease. For these reasons, SLE can affect different aspects of the patient's life, leading to an impairment of HRQOL. Objectives: The aim of the current study was to assess the effect of cutaneous and musculoskeletal symptoms on HRQoL in a cohort of patients with systemic lupus erythematosus in Russian Federation (RENAISSANCE). Methods: Consecutive patients who fulfilled SLICC 2012 criteria for SLE were recruited. Health-related quality of life (HRQoL) was assessed by the validated specific questionnaires LupusQoL-Russian. Disease activity was evaluated by the SLEDAI-2K, and chronic damage by the Systemic Lupus International Collaborating Clinics Damage Index score (SDI). Results: 328 Russian SLE patients were enrolled in the study (M/F 30/298, mean age 34.4±11.5 years, mean disease duration 106.3±97.9 months; mean SLEDAI 2K 9.6±8.0; mean SDI 0.2±0.6. Musculoskeletal symptoms were observed in 142 patients, cutaneous and mucosal lesion symptoms -147 patients, respectively. When comparing HRQOL in patients with lesions skin and mucousal revealed (Table 1 ) significant decline HRQoL on the scales "Planning" (58.5 ± 28.9), "Intimate Relationships" (65.9 ± 32.1), "Burden to other" (52.9 ± 26) and "Body Image" (57.4 ± 29.1) of the LupusQol questionnaire compared with the patients without skin and mucosal lesions (p≤0.002; p≤0.001; p≤0.03; p≤0, 0001 respectively). When evaluating HRQoL in patients with SLE and musculoskeletal symptoms (Table 2 ) reduction of almost all scales LupusQoL. Conclusion: Cutaneous and musculoskeletal symptoms in SLE patients were associated with significantly poorer HRQoL. Disclosure of Interests: None declared